PENGARUH INFLASI DAN SUKU BUNGA SBI TERHADAP TABUNGAN MASYARAKAT KOTA PALEMBANG - Rika Aprilawati; Syaipan Djambak; M Komri Yusuf (Jurnal Ekonomi Pembangunan, 2003)
Understanding the public banking habit. in order of saving behavior is critical in designing politicies to promote saving and economic growth.  Inflation is the one of government obstacle for the saving increasing an the Indonesian Bank Certificate or SBI is the one of monetary policy to fixed it. So this study aims to know how the effects of inflation and SBI for saving behavior in Palembang. The basic theory used are the Loanable Funds Theory and Open Market Operation. The quantitative methods using multiple regression methods with two independent variable whereas qualitative methods used to analyze the datas that relationed with this study. As expected, the estimation result shows that inflation have significant negative impact for saving behavior even SBI have significant positive for that. It described by sign in value ofparameter of independent (exogenous) variable. This result is not to be in contradiction with the other former studies.Keywords: inflation, SBI, Interest Rate, and Deposit